Biomaterial-embedded extracellular vesicles improve recovery of the dysfunctional myocardium. (December 2022) - Pezzana, Chloé; Cras, Audrey; Simelière, Fanny; Guesdon, Rose; Desgres, Manon; Correa, Bruna Lima; Peuffier, Ashley; Bellamy, Valérie; Gouarderes, Sara; Alberdi, Antonio; Perier, Marie-Cécile; Pidial, Laetitia; et al.
Abstract: Extracellular vesicles (EV) are increasingly recognized as a therapeutic option in heart failure. They are usually administered by direct intramyocardial injections with the caveat of a rapid wash-out from the myocardium which might weaken their therapeutic efficacy. To improve their delivery in the failing myocardium, we designed a system consisting of loading EV into a clinical-grade hyaluronic acid (HA) biomaterial. EV were isolated from umbilical cord-derived mesenchymal stromal cells. The suitability of HA as a delivery platform was then assessed in vitro. Rheology studies demonstrated the viscoelastic and shear thinning behaviors of the selected HA allowing its easy injection. Moreover, the release of HA-embedded EV was sustained over more than 10 days, and EV bioactivity was not altered by the biomaterial. In a rat model of myocardial ischemia reperfusion, we showed that HA-embedded EV preserved cardiac function (echocardiography), improved angiogenesis and decreased both apoptosis and fibrosis (histology and transcriptomics) when compared to intramyocardial administration of EV alone. These data thus strengthen the concept that inclusion of EV into a clinically useable biomaterial might optimize their beneficial effects on post-ischemic cardiac repair.